Leitura compartilhada e letramento emergente na educação infantil - Conti, Lilian Maria Carminato (2018)
Providing significant learning experiences in reading and writing in order to guarantee that all the students have the same opportunities constitutes one of the greatest challenges of Brazilian Education. The constant contact with children’s storybooks and the adequate preschool teacher intervention during the reading process seem to act favorably toward the development of the Emergent Literacy. Aiming to investigate the Emergent Literacy, this research is divided into two studies developed with preschoolers. The studies were conducted in a Municipal Preschool Education Center, in a medium-sized city of São Paulo state countryside. In the first study, the goal was to identify whether there is a relation between the students’ repertory (related to the abilities of the Emergent Literacy) and the teacher’s perception regarding these repertories. Four teachers and their students – who pertained to the age bracket of the last phase of the Preschool Education program – participated in this study. Each teacher indicated six students, three with low and three with high performances in activities related to reading and writing, totaling 24 participating students. After indication, the teachers answered a questionnaire about each different student, who was also evaluated by the researcher through the Emergent Literacy Scale. In most cases, the teachers’ assessments tended to correspond to the scores from the Scale for the high-performing students, but they were more discrepant from this measurement for the low-performing students. The teachers tended to evaluate these last students with scores worse than the ones from the scale, except in four (from twelve) cases. The second study aimed at replicating a reading and writing teaching program with a shared-reading approach. Three groups of students in the age bracket of the last phase of the Preschool Education program participated, totaling 55 students. Two groups worked with the mentioned teaching program, while the third served as control. The program was developed in the format of shared-reading workshops, performed inside the classrooms and planned together with each teacher. All the workshops followed a guideline in order to guarantee the stimulus to every component of the Emergent Literacy, by means of different activities: 1. familiarization with the books; 2. shared-reading; 3. make-believe story reading and students handling of books. The application of the teaching procedures was conducted in 15 sessions, each lasting from 20 to 30 minutes, three times a week, for two months. The students were evaluated through the Emergent Literacy Scale (pretest and posttest). The results show that the workshops reduced the variability among the participants, making their performance more similar (around the average) in terms of the repertory of the participant groups when compared with the control group. However, even though some students reached maximum or close to the maximum scores, the averages suggest that the groups, as a whole, did not achieve the maximum potential assessed by the Scale. Some adjustments are recommended for the next replications. Implications to the educational practice and to the formation of preschool teachers are discussed, based on the results of both conducted studies.